Associação entre ácido úrico materno com resultados maternos e perinatais na pré-eclâmpsia - Damacena, Andressa Trecenti [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Introdução: Pré-eclâmpsia é uma síndrome sistêmica específica da gestação com etiopatogenia ainda não esclarecida, porém acredita -se ser decorrente de alterações no processo de invasão trofoblástica, com consequente inadequado suprimento sanguíneo uterino e estresse oxidativo do tecido placentário. O aumento da concentração de ácido úrico sérico materno (AU) em mulheres com pré-eclâmpsia tem sido associado com a gravidade da hipertensão, proteinúria e prognóstico materno e perinatal na gestação. Objetivos: Identificar a associação entre a concentração sérica de ácido úrico e resultados maternos e perinatais adversos e correlacionar a concentração sérica do ácido úrico materno com recémnascidos pequenos para idade gestacional e proteinúria materna. Sujeitos e Métodos: Foi realizado estudo retrospectivo, em gestantes com pré-eclâmpsia, as quais foram estratificadas de acordo com a dosagem de ácido úrico sérico em dois grupos: I (inferior a 6 mg/dL) e II (igual ou superior a 6 mg/dL) e avaliados resultados adversos maternos e perinatais. Resultados: No grupo II houve maior frequência de crise hipertensiva(25%), eclampsia(6,9%), síndrome HELPP parcial (7,8%) e síndrome HELLP(6,9%), maior número de recém-nascidos pequenos para idade gestacional(47%), menor peso do recém-nascido, maior porcentagem de óbito fetal(1,8%), de prematuridade(68%) e de índice de Apgar no 1º minuto(38%). Conclusões: Os resultados demonstram que as paciente com ácido úrico elevado apresentam piores resultados adversos tanto maternos quanto perinatais, sendo assim a dosagem de ácido úrico sérico materna associadas a outros exames clínicos e laboratoriais, pode auxiliar nos processos de decisão na prática obstétrica.

Introduction: Preeclampsia is a specific systemic disease of pregnancy with unknown etiology, but it is believed to be due to changes in the process of trophoblastic invasion, leading to an inadequate uterine blood supply and oxidative stress of the placental tissue. Increasing of maternal uric acid serum concentration (UA) in women with pre-eclampsia has been associated with the severity of hypertension, proteinuria and maternal and perinatal outcome on pregnancy. Objectives: Identify the association between serum uric acid and adverse maternal and perinatal outcomes. More specifically, the correlation of maternal UA serum concentration with newborn size for gestational age and maternal proteinuria. Subjects and Methods: Cross observational study in pregnant women with preeclampsia, which were stratified according to dose of serum uric acid into two groups, as follow: I (below 6 mg/dL) and II (greater or equal to 6 mg/dL). Maternal and perinatal adverse outcomes were examined. Results were analyzed by T - Student and chi-square tests and correlations were evaluated by Pearson test. The level of significance used was 5%. Results: In group II there were a greater frequency of hypertensive crisis, eclampsia, partial HELPP syndrome and HELLP syndrome. Also it were observed an increased number of small newborns for gestational age, lower weight of the newborn, the higher percentage of fetal death, prematurity and index Apgar at 1 minute. Conclusions: The results suggest that patients with higher uric acid have worse adverse outcomes both for maternal and perinatal. In conclusion, the dosage of maternal serum uric acid associated with other clinical and laboratory tests can help in the decision on obstetrical practice.
Uric uric association between mother with results and perinatal maternal in preeclampsia
Keywords: Ácido úrico; Complicações maternas; Complicações perinatais; Pré-eclâmpsia; Recém-nascido pequeno para idade gestacional; Uric acid; Adverse maternal outcomes; Adverse perinatal outcomes; Preeclampsia; Small for gestational age